Absorber Hydraulies Modifieation for Zero-Foaming ofMDEA Solutions - Sekhon, Ajitpal Singh (Universiti Teknologi Petronas, 2010)
This thesis describes the research carried out to solve the foaming issues in Malaysia LNG Sdn. Bhd. with its Acid Gas Removal Units. The absorber column hydraulics and design is found to be not suitable for usage of MDEA solvents which gives a higher absorption capacity. A thorough study of absorber hydraulics and parametric study on foaming behavior is carried out. Modification for the hydraulics design is calculated and justified to avoid foaming. The report consist of four chapters that cover the introduction of the project, literature review of related topics, project methodology, Project Progresses and finally the conclusion. The introduction part mainly discussed about the background of the study of foaming issue in the acid gas removal unit using MDEA solvent. Objectives and scope of the study is also defined here to specify the area of study. Chapter 2 of the report describes more on the literature review of Hydraulic Limitations, Foaming Tendency, Foaming Stability, Column Hydraulics Design Consideration, Foaming Factor, and Acid Gas Absorber (Tray column) Internal Design. The methodology and project work will be covered in the Chapter 3 of the report. In this part, the procedure identification of the study, and tooVsoftware required is discussed. The methodology consists of work on reviewing design consideration for absorber column, study properties of MDEA solvents and foaming mechanics. The deliverable from this research is to propose design of absorber column with detailed calculation and modeling which is robust from MDEA solvent foaming. Chapter 4 describes the Results and Discussion. Information from the Excel Modeling is made known here and communicated through tables and calculation basis. Finally, the project conclusion is stated in the report together with the references used for research work on this project.